СОСТОЯНИЕ ВЕГЕТАТИВНОЙ НЕРВНОЙ СИСТЕМЫ В УСЛОВИЯХ НАГРУЗКИ У ЖЕНЩИН НА СЕВЕРЕ РФ : AUTONOMIC NERVOUS SYSTEM STATUS AT PHYSICAL ACTIVITY OF WOMEN LIVING IN THE NORTH TERRITORIES OF RUSSIA - БАШКАТОВА Ю.В.; ЧЕМПАЛОВА Л.С.; ТРОФИМОВ В.Н.; АКСЕНОВА Ю.А.; ПОНОМАРЕВА Н.И. (Вестник новых медицинских технологий, 2020)
Проблема увеличения продолжительности жизни жителей Севера РФ требует детального изучения особенностей регуляции сердечно - сосудистой системы обследуемых. Цель исследования. Изучение реакции симпатической и парасимпатической вегетативной нервной системы на дозированную физическую нагрузку. Материалы и методы. Исследовалась группа женщин (средний возраст 28 лет) по параметрам симпатической и парасимпатической систем регуляции сердечно - сосудистой системы в спокойном состоянии и после 30 - ти приседаний. С помощью аппарата «Элокс-01» регистрировали по 5 минут параметры кардиоинтервалов (по 15 раз у каждого человека). Для каждого испытуемого строилась матрица парных сравнений выборок параметров кардиоинтервалов и рассчитывались числа к пар выборок, которые можно отнести к одной генеральной совокупности. Одновременно рассчитывались и параметры квазиаттракторов для этих показателей. Результаты. Установлено, что числа к для всех испытуемых в режиме 15 - ти повторов имеют разные и крайне низкие значения, что доказывает эффект Еськова-Зинченко и для сердечно - сосудистой системы. Одновременно, числа к в этих матрицах существенно изменялись как по группе, так и индивидуально после нагрузки. Заключение. Выборки параметров симпатической и парасимпатической систем не могут демонстрировать однородность как отдельного человека, так и целой группы. Необходимо многократно повторять регистрацию этих параметров для учета неоднородности групп и эффекта Еськова - Зинченко. : The problem of increasing the life expectancy of residents of the North of the Russian Federation requires a detailed study of the characteristics of the regulation of the cardiovascular system of the subjects. The research purpose was to study the response of the sympathetic and parasympathetic autonomic nervous system to dosed physical activity. Materials and methods. A group of women was studied (average age 28 years) according to the parameters of the sympathetic and parasympathetic systems of regulation of the cardiovascular system in a calm state and after 30 squats. Using the «Elox-01» apparatus, the parameters of cardio intervals were recorded for 5 minutes (15 times for each person). As a result, a matrix of pairwise comparisons of samples of parameters of cardio intervals was built for each subject, and the numbers k of pairs of samples were calculated, which can be attributed to one general population. At the same time, the parameters of pseudo-attractors for these indicators were calculated. Results. It was found that the numbers k for all subjects in the mode of 15 repetitions have different and extremely low values, which proves the Eskov-Zinchenko effect for the cardiovascular system. At the same time, the numbers k in these matrices significantly changed both in the group and individually after the load. Conclusions. Parameter samples of the sympathetic and parasympathetic systems cannot demonstrate the homogeneity of both an individual person and a whole group. It is necessary to repeat the registration of these parameters many times to take into account the heterogeneity of the groups and the effect of Eskov-Zinchenko.